A resource dependency framework for innovation and internationalization of family businesses: Evidence from India. Issue 2 (5th June 2017) - Singh, Ramanjeet; Kota, Hima Bindu
Abstract : Purpose: To compete and to survive in this era of globalization, organizations, including family businesses, need to have competitive advantage, and innovation and internationalization are some of the ways to achieve this. This paper aims to analyze whether family businesses innovate and internationalize more than non-family businesses and further analyses the type of family businesses "age-wise" and "size-wise" that innovate and internationalize more. Design/methodology/approach: The study is empirical in nature. The period of study is 11 years, from 2005 to 2015 (both years inclusive). The sample is chosen from Bombay Stock Exchange (BSE) 500 index, a broad-based index in India, covering about 20 industries of the economy. The present study uses multiple regression models to find the innovativeness and internationalization of family businesses. The dependent variables are R&D (proxy for innovativeness) and FXINC (proxy for internationalization). The independent variables are FB (variable that defines whether a business is family business or non-family business); FBAGE (variable that defines the age of the family business); and FBSIZE (variable that defines the size of the family business). The other control variables used in in the study are TA (total assets), REV (revenue), CR (current ratio), QR (quick ratio), DER (debt-equity ratio) and RONW (return on net worth). Fixed effects model was used to understand the innovativeness and internationalization of family businesses. Both industry and year fixed effects were used. SPSS 20.0 version is used for the analysis. All results are heteroscedastic consistent using Breusch–Pagan test. Findings: It is found that family businesses are more innovative and internationalized when compared to non-family businesses. The results are consistent with the resource-based theory where it is found that family businesses are entrepreneurial in nature (Salvato, 2004; Zahra et al., 2004; Kellermanns and Eddleston, 2006) which makes them more innovative. It was also found that within the family businesses, younger firms were more innovative and internationalized than older firms. This can be explained by the theory of "learning advantages of newness", according to which younger firms are more flexible, eager to learn, have less internal resistance and are able to adapt to the changing environment much faster. Originality/value: During the studies, the authors have found that there is no conclusive evidence on the innovativeness and internationalization of family businesses. Further, there are apparently negligible studies that analyze what type of family businesses, age wise (younger or older firms) and size wise (smaller or larger firms) use the strategy of innovation and internationalization to grow. The present study analyses the innovativeness and internationalization of family businesses when compared to non-family businesses and also studies the type of family businesses (age wise and size wise) that are more innovative and internationalized.